Distress and well-being in dentists: performance of a screening tool for assessment - Subha Giri; Colin P. West; Tait Shanafelt; Daniel Satele; Liselotte N. Dyrbye (Nature Publishing Group, 2024)
Abstract Objectives Dentists' well-being is being challenged today by many factors. However, effective screening tools to assess their distress and well-being are yet to be validated. The present study aims to evaluate the ability of the Well-Being Index (WBI) to identify distress and stratify dentists' well-being and their likelihood for adverse professional consequences. Method and materials A convenience sample of dentists completed a web-based 9-item WBI survey along with other instruments that measured quality of life (QOL), fatigue, burnout, and questions about suicidal ideation, recent dental error, and intent to leave their current job. Results A total of 597 dentists completed the survey. The overall mean WBI score was 2.3. The mean WBI score was significantly greater in dentists with low QOL than among dentists without low QOL (4.1 vs 1.6, p < 0.001). Dentists with extreme fatigue, burnout, and suicidal ideation had significantly higher mean WBI score than those without distress (all p < 0.001). WBI score stratified the dentists' likelihood of reporting a recent dental error and intent to leave their current job. Conclusion The WBI may be a useful screening tool to assess well-being among dentists and identify those in distress and at risk for adverse professional consequences.